ANALYSIS OF STUDENT LEARNING MOTIVATION IN CHEMICAL LEARNING - Jami, Jami (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2020)
The purpose of this survey is to find out how much the motivation of students in class XI MIA learning chemistry at MAN 1 Tanjung Jabung Timur. This type of research is a survey with cross sectional design type. The subjects of the study were 32 students of class XI MIA. Research instruments using a questionnaire distributed to students and observations made while learning chemistry took place. Analysis of the results of research data in the form of quantitative data analyzed with descriptive statistics, so that it can present the results of research with distribution tables and piechart diagrams. The results of the questionnaire data with an average score obtained by students by 71 points, and included in the category quite well. Students in class XI MIA MAN 1 Tanjung Jabung Timur get survey results for each category as follows: The learning motivation of class XI MIA students at MAN 1 Tanjung Jabung Timur was obtained by an average of 71 points, which was categorized as fair. The results of the questionnaire data are presented in five categories. Unacceptable category got a percentage of 0%, less category got a percentage of 13%, fair category got a percentage of 62%, good category got a percentage of 25%, and very good category got 0%. Keywords: learning motivation, chemistry, analysis